Marital contingence according to aggression and empathy rates - Атраментова, Л. О.; Лучко, К. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The article contains the results of the study of a structure-forming role of aggression and empathy in the population of Kharkov city. It has been established that aggression and empathy are in the positive correlation connection among both men (r=0,08) and women (r=0,12). The level of direct correlation index has turned out to be higher (0,28–0,31) than the level of cross correlation index (0,20–0,23). The strongest attraction is between the spouses by level of empathy (K=0,18), for other combinations connecting K index is located at the level of 0,13–0,14.